Interference With Coagulation Cascade as a Novel Approach to Counteract Cisplatin-Induced Acute Tubular Necrosis; an Experimental Study in Rats - Ewees, Mohamed G.; Messiha, Basim A. S.; Abo-Saif, Ali A.; Bayoumi, Asmaa M. A.; Abdel-Bakky, Mohamed S. (Frontiers in Pharmacology, 2018)
Blood coagulation plays an important role in the pathophysiology of different diseases. In spite of massive research regarding cisplatin-induced nephrotoxicity, the role of coagulation cascade in such toxicity is still questionable. Here, we aim to investigate the role of blood coagulation in the initiation of cisplatin-induced acute renal tubular necrosis. Moreover, the role of the anticoagulant rivaroxaban against such toxicity was investigated. Briefly, animals were classified into seven groups, 8 rats each. Group 1 served as normal control group, groups (2-7) received i.p. single doses of cisplatin (6 mg/kg), groups (6-7) were treated with rivaroxaban (5 and 7 mg/kg, p.o., respectively) seven days before cisplatin injection and completed for four days. Animals in groups (2, 3 and 4) were sacrificed after 1, 2 and 3 days of cisplatin injection, respectively, while groups (1, 5, 6 and 7) were sacrificed after 4 days of cisplatin injection. Serum cystatin-c, urea, creatinine and γ-glutamyl transferase, urinary Lipocaline-2 and KIM-1 protein densities, as well as glomerular filtration rate (GFR) were assessed. Immunofluoresence examination of glomeruli fibrin and tissue factor (TF) was also performed coupled with a histopathological study. Cisplatin administration increased expression of fibrin and tissue factor starting 24 hours of cisplatin injection even before renal failure markers elevated. Leukocytosis, thrombocytopenia and increased prothrombin time were also observed. Cisplatin also induced tubular damage evidenced by increased serum cystatin-c, urea and creatinine with significant decrease in GFR and GGT activity. Rivaroxaban significantly decreased elevation of fibrin and TF with significant reduction in serum creatinine, BUN and cystatin-c levels. Rivaroxaban also significantly improved hematological markers and histological features as well. This study showed that blood coagulation plays an important role in the pathophysiology of cisplatin-induced acute renal tubular damage. Interference with coagulation cascade may be a promising nephroprotective strategy against chemical nephrotoxicity.